Careers in cross-cultural context : a study of Sri Lankan immigrants in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Management at Massey University, Albany, New Zealand - Tharmaseelan, Nithiyaluxmy (Massey University, 2005)
This study considered migrants’ career outcomes as the result of their adjustments in terms of culture and career adaptation along with other positive attributes they brought on their arrival as well as developing in their new country. It considered that career is the property of individuals and managing it successfully is the responsibility of individuals themselves. Prior research into migrants’ issues and careers was used as the basis of this study and a model for analysis was developed using such issues. The resultant model included the wider life of migrants. A questionnaire including reliable measures of key variables was developed based on the literature. Two hundred and twenty-one Sri Lankan migrants completed the pilot tested survey. The results were analysed using factor analysis, tests of association and multiple regression analysis at the first stage to formulate a less complex model. Structural equation modelling was then used to confirm the relationships assumed between different variables. Although some of the relationships and/or variables assumed initially were removed from the model, the final model explained strong links between the variables that remained. Qualification gained before migration and career self-efficacy were found to be the most significant variables in explaining job satisfaction before migration. Usefulness of prior knowledge, skills and habits, efforts made towards career, education in New Zealand, information seeking, length of time in New Zealand and overseas experience had the greatest influence on current job level. Current job level, length of time in New Zealand and overseas experience were found to be the most significant variables explaining subjective career success after migration. Adapting to New Zealand culture was found to be significant in explaining only the career satisfaction after migration. It was also found that migrants’ career outcomes (success and satisfaction) after migration were significant variables in explaining overall career satisfaction of this migrant group: however, with the exception of job satisfaction, career outcomes before migration did not play a significant role in determining overall career satisfaction. The implications of the present study were considered, from both migrants’ perspective and that of New Zealand as the host society. A number of possible practical strategies relevant to migrants, community organisations and policy makers and authorities were suggested. Several potential avenues for future researches were identified and discussed. Thus, it is expected that this study will contribute to better career outcomes of migrants in New Zealand.
Keywords: Career success; Career satisfaction; Acculturation; Migration; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management